On the nomenclatural type of Triticum durum (Poaceae: Triticeae) - Ferrer-Gallego, P. Pablo; Laguna, Emilio; Obón, Concepción; Alcaraz, Francisco; Rivera, Diego (Phytotaxa, 2022)
The nomenclatural type of Triticum durum is discussed. The name is lectotypified using a specimen collected in the North of Africa and preserved at Herb. P.